2017
DOI: 10.4236/ojmm.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in <i>Campylobacter</i> Isolated from Patients with Gastroenteritis in a Teaching Hospital in Ghana

Abstract: Campylobacter is a leading causal agent of bacterial enteritis worldwide, but its prevalence is not well documented in Ghanaian hospitals. This study isolated Campylobacter species from patients with enteritis or urinary tract infections attending Komfo Anokye Teaching Hospital and assessed the antibiogram profile of isolated species. Two hundred and two (202) in-patients and outpatients samples of all age groups diagnosed with enteritis or UTI infections were analyzed from May 2013 to August 2013. Campylobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 22 publications
(20 reference statements)
10
51
5
Order By: Relevance
“…This is corroborated by previous studies, which reported high campylobacter prevalent in male patients compared to female patients (Friedman et al, 2000;Fitzgerald et al, 2011). However, some studies found that females have higher risk of getting infected by Campylobacter than males (Gillespie et al, 2006;Karikari et al, 2017).The isolated strains in our study showed considerable resistance to ampicillin (26.4%), to tetracycline (30.5%) whereas the resistances to ciprofloxacin, erythromycin and gentamicin were relatively low (0.5-1%). These results are in agreement with 30.7% resistance to tetracycline, 26.9% to ciprofloxacin, 1.7% to erythromycin and 0.9% to gentamicin previously reported in France (Gallay et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is corroborated by previous studies, which reported high campylobacter prevalent in male patients compared to female patients (Friedman et al, 2000;Fitzgerald et al, 2011). However, some studies found that females have higher risk of getting infected by Campylobacter than males (Gillespie et al, 2006;Karikari et al, 2017).The isolated strains in our study showed considerable resistance to ampicillin (26.4%), to tetracycline (30.5%) whereas the resistances to ciprofloxacin, erythromycin and gentamicin were relatively low (0.5-1%). These results are in agreement with 30.7% resistance to tetracycline, 26.9% to ciprofloxacin, 1.7% to erythromycin and 0.9% to gentamicin previously reported in France (Gallay et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, our results are lower than 48.0% resistant to ampicillin reported by Gallay et al (2008). High resistance rates to tetracycline have been described in Ghana (92.3 -100%, Karikari et al, 2017), in Spain (72%; Prats et al, 2000) in human isolates. At the global scale, the tetracyclines are a heavily used class of antibiotics both in human and in veterinary medicine (Iovine, 2013).…”
Section: Discussioncontrasting
confidence: 68%
“…The study also agrees with [14] who reported a low resistance (18%) of Campylobacter species to gentamycin in Tanzania. The high resistance of Campylobacter coli to Erythromycin (100%) in this study agrees with [13] who reported a 100% resistance of C. coli to Erythromycin.…”
Section: Antibiotic Resistance Pattern Of Campylobacter Species Isolasupporting
confidence: 92%
“…This low resistance observed in Imipenem could be due to the fact that this Carbapenem is able to resist hydrolysis by βlactamases, modification in penicillin-binding proteins and decreased in porin uptake leading to inhibition of Campylobacter cell wall synthesis [3]. This finding was in agreement with [20,17,13] who reported a 100% susceptibility of all Campylobacter species to Imipenem.…”
Section: Antibiotic Resistance Pattern Of Campylobacter Species Isolasupporting
confidence: 84%
“…Antibiotic addition to feeds has also been found to affect intestinal microflora (Niewold ), which have been increased the demands for effective substances to reduce pathogenic bacteria and improve animal health (Kroismayr et al ). Last decade, numerous reports demonstrated the development of antibiotic resistance that started to impact negatively on our ability to treat some human pathogens (Karikari et al ). Thus, medicinal plants and herbs are being investigated as a potential solution to promote animal performance without fostering antibiotic resistance (Baurhoo et al ).…”
Section: Introductionmentioning
confidence: 99%